Feasibility of Informed Consent for Computed Tomography in Acute Trauma Patients. (24th March 2017) - Moore, Nicole; Patel, Bhavesh; Zuabi, Nadia; Langdorf, Mark I.; Rodriguez, Robert M.
Abstract: Background: Computed tomography (CT) is common for trauma victims, but is usually done without informing patients of potential risks or obtaining informed consent. Objective: The objective of this study was to determine the feasibility of two elements (time and normal level of alertness) necessary for informed consent for CT in adult trauma patients. Methods: We conducted this prospective observational, two‐phase cohort study at two urban, Level I trauma centers. In the first phase, we determined the median time needed to obtain informed consent for CT by performing sham consent on 11 injured patients at each site. In the second phase, we observed all adult trauma activation cases that presented during specified time blocks and recorded Glasgow Coma Scale (GCS) scores and the time available for consent (TAC) for CT—defined as the time between the end of the secondary trauma survey and when the patient left the resuscitation room to go to CT. We defined, a priori, feasible consent cases as those in which the patient had a GCS of 15 and a TAC greater than the median sham consent time at that site. Results: The median times for sham CT consent at the two sites were 3:36 and 2:09 minutes:seconds (range = 1:12–4:54). Of the 729 trauma patients enrolled during phase II, 646 (89%) had a CT scan, and of these 646 patients, 461 (71.4% [95% confidence interval = 67.8%– 74.7%]) met feasible consent criteria. Of the 185 patients who failed to meet feasible consent criteria, 171 (92.4%) had a GCS < 15, one (0.5%) had a TAC less than the sham consent time, and 13 (7.0%) had both. Conclusion: We found that informed consent for CT was likely feasible in over two‐thirds of acute, adult trauma patients.